Employing Parasite Against Cancer: A Lesson From the Canine Tapeworm Echinococcus Granulocus - Wang Guan; Xiaoqin Zhang; Xiao Wang; Shun Lu; Jun Yin; Jinxin Zhang (Frontiers Media S.A., 2019)
Cystic echinococcosis (CE), a devastating zoonotic condition caused by the tapeworm Echinococcus granulosus, remain a significant public health problem worldwide. However, after a negative correlation between solid tumor and CE has been incidentally discovered, accumulating evidence have suggested that this parasite may induce anticancer effect through activating host immune response and secreting molecules with anticancer potential, which may provide some new understanding for immunotherapy. This article will review the evidence supporting the anticancer effect of E. granulosus and its underlying mechanisms and discuss the possible implications in immunotherapy.